Solar water heating for social housing: Energy analysis and Life Cycle Assessment - Souliotis, Manolis; Panaras, Giorgos; Fokaides, Paris A.; Papaefthimiou, Spiros; Kalogirou, Soteris A. (My University, 2018)
This work presents the study of two innovative solar water heating systems, integrated on the facades and the roof of a social house building. One of the systems combines collector and storage tank in a single unit, called Integrated Collector Storage solar water heater; the other one comprises a photovoltaic and a thermal collector known as Hybrid Photovoltaic/Thermal device, in which the produced energy support both thermal and electrical needs. The analysis has considered the integration of the studied solar systems on building's envelope, investigating the effect of these systems in terms of building's thermal load along with their capacity to cover the hot water and electrical needs. The energy behavior of the building, as well as the energy output of the solar systems are investigated through simulation analysis for two cities (Nicosia, Cyprus and Athens, Greece) and three orientation modes (South, East and West). The results show that, after the interventions, the energy demands of the building for space heating and cooling are decreased at about 10%, while the hot water and electrical demands are covered up to 80 and 50%, respectively. The energy contribution of the respective solar systems with regard to the buildings’ energy demand is evaluated through Life Cycle Assessment; the respective analysis allows the evaluation of the environmental impacts during the entire life cycle of the considered systems.
Keywords: Social house; Building Integrated Solar Thermal Systems (BISTS); Energy analysis; Integrated Collector Storage (ICS) solar water heaters; Hybrid Photovoltaic/Thermal (PV/T) solar systems; Life Cycle Assessment (LCA)